The next great war? : the roots of World War I and the risk of U.S.-China conflict - Rosecrance, Richard N.; Miller, Steven E. (The MIT Press, 2014)
Experts consider how the lessons of World War I can help prevent U.S.--China conflict.
Keywords: World War, 1914-1918 -- Causes.; United States -- Foreign relations -- China.; China -- Foreign relations -- United States.; Guerre mondiale, 1914-1918 -- Causes.; États-Unis -- Relations extérieures -- Chine.; Chine -- Relations extérieures -- États-Unis.; HISTORY -- Europe -- Western.; Diplomatic relations; War -- Causes; China; United States; 1914-1918; SOCIAL SCIENCES/Political Science/General; HUMANITIES/History; SOCIAL SCIENCES/Political Science/International Relations & Security